Molecular Cytogenetic Identification of a Novel Wheat–Thinopyrum ponticum 1JS (1B) Substitution Line Resistant to Powdery Mildew and Leaf Rust - Li, Mingzhu; Wang, Yanzhen; Liu, Xiaojuan; Li, Xingfeng; Wang, Honggang; Bao, Yinguang (Frontiers in Plant Science, 2021)
Thinopyrum ponticum (2n = 10x = 70), a wild relative of wheat with high tolerance to both biotic and abiotic stresses, has been wildly used in wheat genetic improvement. SN19647, a disomic substitution line, was derived from a cross between Triticum aestivum and the wheat–Th. ponticum partial amphiploid line SNTE20 (2n = 8x = 56). It was evaluated for disease resistance and characterized viasequential fluorescence in situ hybridization (FISH)-genomic in situ hybridization (GISH) and molecular markers. The results showed that SN19647 carried resistance to both powdery mildew and leaf rust. It contained 42 chromosomes with a pair of wheat chromosome 1B replaced by a pair of JS chromosomes from Th. ponticum. In addition to chromosomal substitution event, structural variation also occurred on wheat chromosomes 2A, 5A, 6B and 7B. Based on marker analysis, 19 markers specific to the JS chromosome were obtained, of which seventeen markers belonged to homoeologous group one. These results indicated that SN19647 was a 1JS (1B) substitution line. Compared with the known 1JS (1D) substitution line CH10A5, it was found that there were 17 markers generating different specific bands to Th. ponticum, confirming the novelty of the 1JS chromosome in SN19647. Therefore, SN19647, resistant to powdry mildew and leaf rust, was a novel 1JS (1B) substitution line that can be used in wheat genetic improvement.